Insulin resistance, impaired postprandial lipid metabolism and abdominal obesity. A deadly triad. - Frayn, K (2002)
OBJECTIVE: To review three 'emerging risk factors' for coronary heart disease, the physiological and pathophysiological mechanisms involved, and their inter-relationships. BACKGROUND: Classical risk factors for coronary heart disease cannot adequately explain the high incidence of this disease. Abdominal obesity and impaired postprandial lipid metabolism have long been recognised as associates of coronary heart disease but only relatively recently has their importance as risk markers been established. Insulin resistance is now often seen as a common theme underlying many factors predisposing to coronary heart disease (CHD). MECHANISMS: The mechanisms by which each of these markers relates to coronary heart disease may have common aspects. Specifically, they are all associated with a characteristic dyslipidaemia involving elevation of plasma triacylglycerol concentrations, reduction of high-density lipoprotein cholesterol (HDL-cholesterol) and the presence of small, dense low-density lipoprotein particles that may carry particular risk of atherogenesis. Insulin resistance is also associated with hypertension and impairment of endothelial function, and with a procoagulant state. TREATMENT: No specific or separate pharmacological treatment of any of these conditions separately has been shown to reduce the risk of CHD although each can be manipulated. Lifestyle modification, with increased physical activity and dietary change, may offer the best hope of primary prevention but to achieve this, interventions at government level rather than advice from individual physicians would probably be required. CONCLUSIONS: Abdominal obesity, impaired postprandial lipid metabolism and insulin resistance are all inter-related risk markers for CHD. They seem to reflect lifestyle in the developed and developing worlds and perhaps modification of lifestyle holds the greatest hope for their amelioration in the future.